Re-Evaluating The Idea Of A Malaysian Architectural Identity Towards A Sustainable Environment - Nurakmal, Abdullah@ Goh Tuo Ho; Mazlan, Mohd Tahir; Surat, M.; Usman, Iliyasu; Norngainy, Mohd Tawil; Muhammad, Nor; Che-Ani, A. I. (2010)
This paper suggests the rethinking on the approaches and architectural experimentation that had been conducted by the Malaysian architectural profession towards the search for a national identity in architecture towards a sustainable community. The first part will discussed on the attempt and discourse that had been conducted which involved the public and private sectors. Since achieving our independence, architects, patrons and the public had conducted experimentation on the various approaches and aspects pertaining to the issue of a Malaysian architectural identity through discourse, writings and architectural design. Comments and critiques were received from the public as well as from architectural commentators and architectural historians from locals and abroad. It was critically claimed that architectural practice in our country still lacks depth in its theoretical approach and weak in it construction implementation which lead to a crisis in the profession. The crisis on the Built Environments’ education programmes over the last two decades also has led the professional practice of architecture having reached sub standard level with no proper philosophical and theoretical approach. The failure on the quest for an identity in architecture for the last four decades was attributed to architects and other implementers failing to disseminate the ideas and intentions to the grass roots level. No records or evident can be found to support the notion that the ideas of searching for a national identity in architecture has been delivered to grass root or public level. It is imperative that current generation of architects and implementers of the profession re-evaluating the idea and making further mission successful.